2021
DOI: 10.3390/atmos12050587
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature Variability over the Tropical Indian Ocean during the ENSO and IOD Events in 2016 and 2017

Abstract: 2016 and 2017 were marked by strong El Niño and weak La Niña events, respectively, in the tropical East Pacific Ocean. The strong El Niño and weak La Niña events in the Pacific significantly impacted the sea surface temperature (SST) in the tropical Indian Ocean (TIO) and were followed by extreme negative and weak positive Indian Ocean Dipole (IOD) phases in 2016 and 2017, which triggered floods in the Indian subcontinent and drought conditions in East Africa. The IOD is an irregular and periodic oscillation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…in an upwelling area of northern Costa Rica; according to their results, coral fragments grew faster during the non‐upwelling season. However, during January 2016, SST was 1.4°C above historic temperature in the study area and remained hotter thorough the year associated with El Niño 2016–2017 (Khan et al 2021). It may be argued that an anomalously hot period could reduce the upwelling cold water stress for corals and allow them to grow faster; in contrast, the hottest SST records could hamper coral growth in summer.…”
Section: Discussionmentioning
confidence: 94%
“…in an upwelling area of northern Costa Rica; according to their results, coral fragments grew faster during the non‐upwelling season. However, during January 2016, SST was 1.4°C above historic temperature in the study area and remained hotter thorough the year associated with El Niño 2016–2017 (Khan et al 2021). It may be argued that an anomalously hot period could reduce the upwelling cold water stress for corals and allow them to grow faster; in contrast, the hottest SST records could hamper coral growth in summer.…”
Section: Discussionmentioning
confidence: 94%
“…Dalpadado et al, (2021) pointed out that sea surface temperature (SST) has increased in last two decades and net primary production (NPP) showed large inter-annual variability in northern and central regions of the Indian Ocean, with slightly decreasing trends in a few northern regions. Furthermore, strong El Niño and weak La Niña events in the Paci c signi cantly impacted the sea surface temperature (SST) in the tropical Indian Ocean (TIO) and were followed by extreme negative and weak positive Indian Ocean Dipole (IOD) phases reported in 2016 and 2017 respectively (Khan et al, 2021). The inter-annual peaks in the catch rates including the extraordinary increase in the catch rates in 2017 could probably be resulted with extremely favorable oceanographic conditions such as increase of Chlroophyll-a (Marsac and Demarcq, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Empirical Orthogonal Function (EOF), also known as Eigenvector Analysis or Principal Component Analysis, is a method for extracting the eigenvector of variables. It was first applied to climatology and meteorology by Lorenz in the 1950s and is now widely used to highlight potential physical mechanisms related to climate variability [6,16,17]. The spatial patterns (EOFs), the temporal series (PCs), and the eigenvalues are the outputs of the EOF analysis.…”
Section: Empirical Orthogonal Function (Eof)mentioning
confidence: 99%
“…Atmosphere 2021, 12,1446 2 of 20 In recent years, a lot of research has been conducted to detect the possible relation between large-scale climate phenomena and droughts or floods in specific geographical locations [2,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Wahiduzzaman concluded that major flood events over Bangladesh occurred during the monsoon period, and most of them occurred under the La Niña condition [24].…”
Section: Introductionmentioning
confidence: 99%